The early ʻAbbāsī Empire - Ṭabarī 838?-923 (Cambridge University Press, 1988)
The revolutionary Abu Ja'far al-Mansur came to power in 754 AD and died in 775, after destroying every threat to his own supremacy. Here are the reminiscences of those who witnessed these years, woven by the great historiographer al-Tabari (d. 923) into a vivid account and translated for the first time